"A Regional Conservation Manifesto", The Burra Charter and the Australian Re-invention of Urban Heritage Management, ca. 1975–1985. (3rd July 2017) - Lesh, James P.
ABSTRACT: Since the 1970s Australian heritage practitioners – academics, consultants and policymakers – have constituted a robust urban heritage management field. Particularly via the 1979 Australia ICOMOS Burra Charter, this field has equally impugned and influenced regional and international urban heritage practice. Examining the archives of leading Australian heritage protagonists, this article argues that the Australian innovations of the 1970s and 1980s were prompted in part by a backlash against European heritage ideas and practices, after Australian heritage practitioners found themselves side-lined at European meetings. Over subsequent decades, the Australian heritage management events of this historical period have proven significant for local, regional and international conservation efforts in cities and beyond.